Analysis of Factors Influencing Work Productivity in Warehousing and Logistics Companies in Indonesia (Literature Study) - Peppy Fachrial; Aswanti Setyawati; Sarinah Sihombing; Primadi Candra Susanto (Dinasti Publisher, 2026)
This study aims to analyze the influence of self-efficacy, competence, and discipline on employee work productivity through job satisfaction in warehousing and logistics companies in Indonesia. Job satisfaction is seen as an important factor that influences employee attitudes, motivation, and performance, especially in the warehousing and logistics industry that demands speed, accuracy, and operational efficiency. This study uses a descriptive qualitative approach with a literature review method. The data used are secondary data amounting to 30 scientific articles sourced from reputable national and international journals. The analysis was carried out by examining the relationship between job satisfaction indicators, namely satisfaction with work, work environment, and rewards, with work productivity indicators including quantity of work results, quality of work results, and work time efficiency. The results of the study indicate that: 1) Self-efficacy has a positive effect on job satisfaction; 2) Competence has a positive effect on job satisfaction; 3) Discipline has a positive effect on job satisfaction; 4) Self-efficacy has a positive effect on work productivity; 5) Competence has a positive effect on work productivity; 6) Discipline has a positive effect on work productivity; 7) Job satisfaction has a positive effect on work productivity; 8) Self-efficacy has a positive effect on work productivity through job satisfaction; 9) Competence has a positive effect on work productivity through job satisfaction; 10) Discipline has a positive effect on work productivity through job satisfaction.